2003
DOI: 10.1124/jpet.102.042416
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Endotoxin and Dexamethasone on Enrofloxacin Pharmacokinetic Parameters in Swine

Abstract: The impact of Escherichia coli-derived lipopolysaccharide (LPS) on the pharmacokinetic parameters of enrofloxacin in swine was assessed to determine whether this model would substitute for a pleuropneumonia infection model for pharmacokinetic evaluation of drugs. All animals received a single i.v. dose of enrofloxacin (5 mg/kg). Half the animals also received dexamethasone (0.5 mg/kg) to determine the impact of inflammation on any changes in enrofloxacin pharmacokinetics, as most of the effects of LPS are due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 23 publications
3
34
1
Order By: Relevance
“…Possibly, this is due to the different types of inflammation inducers used (LPS vs. E. coli bacteria); E. coli may induce more cytokines mediating more cell signaling pathways. It has been pointed out that LPS is not a generic substitute for bacterial infection to study its effect on P-gp expression, function and on drug pharmacokinetics [26]. Alternatively, this might be due to different species used (chickens vs. rats).…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, this is due to the different types of inflammation inducers used (LPS vs. E. coli bacteria); E. coli may induce more cytokines mediating more cell signaling pathways. It has been pointed out that LPS is not a generic substitute for bacterial infection to study its effect on P-gp expression, function and on drug pharmacokinetics [26]. Alternatively, this might be due to different species used (chickens vs. rats).…”
Section: Discussionmentioning
confidence: 99%
“…However, given that we have demonstrated that the BBB transport of colistin does not appear to be limited by the action of P-gp, any increase in the brain uptake of colistin following LPS administration is likely to be a result of increased paracellular diffusion. Administration of LPS also served another important purpose in this study in that its effects can mirror the infected state in which colistin is normally clinically used (25). The reduced BBB integrity during the infected state may be beneficial as it may lead to increased antibiotic concentrations in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other investigators have detected colistin in the CSF of infected patients following systemic administration (1,15,21), whereas we have previously observed limited brain uptake in healthy mice although this could also be attributed to species differences and/or differences between BBB and blood-CSF barrier penetration profiles. While the impact of infection on BBB transport may be investigated by inducing bacteremia in mice, bacterial lipopolysaccharide (LPS) is often used to mimic the infective state as it results in the release of proinflammatory cytokines (25,31). Several studies have shown that BBB disruption can be induced by bacterial LPS, leading to increased brain uptake of compounds that normally exhibit limited access into the CNS (3,22).…”
mentioning
confidence: 99%
“…Single daily doses of the three FQs for 3 consecutive days with simulated half-lives (t 1/2 ) consistent with those reported in pigs were used: 12.5 h for DIF (33,34), 10.6 h for ENR (35,36) and 8 h for MAR (37). The doses were selected to include the achievable area under the curve (AUC) and maximum plasma concentration (C max ) over a 24-h dosing interval at the recommended clinical doses (1 to 5 mg/kg of body weight for DIF, 2.5 to 5 mg/kg for ENR, and 2 mg/kg for MAR) in pigs.…”
Section: Methodsmentioning
confidence: 99%